Effects of Heat Treatments of Rosella Seeds (Hibiscus Sabdariffa, Linn) and the Presentation of Diets Containing them on Zootechnical and Economic Performances of Broilers in Dakar Region (Senegal): - Ayssiwede, Simplice Bosco; Abodi, Koffi Elemawussi; Atchiwassa, Sodjinin; Bonou, Mahou-hognon Cyrille; Missohou, Ayao (Indian Journal of Animal Nutrition, 2023)
This study carried out in Sangalkam from March to April 2019, aims to assess the effects of heat treatments of rosella seeds and the presentation of diets containing them on growth performance and economic margins of broilers. It involved 400 unsexed Coob500 strain chicks of two-weeks-old, randomly distributed into 8 groups of 50 birds each, corresponding to 8 iso-protein and iso-energetic experimental diets consisting of 4 floury (HSF0, HSCF15, HSTF15, HSBF15) and 4 granulated (HSG0, HSCG15, HSTG15, HSBG15) containing respectively 0% (control), 15% of raw, roasted and boiled rosella seeds in partial substitution of groundnut cake. At 6 weeks of age, data obtained per dietary treatment, were subjected to one-way ANOVA, completed by Duncan’s Multiple Range Test at 5% error risk level. The results showed that the live body weight, daily feed intake and carcass weight of broilers fed granulated diets (HSG) were higher (p<0.05) respectively than those of birds from floury diets (HSF). It was the same trend with the average daily weight gain and dressing carcass, except for roasted seed diets (HST15) where these last were similar. The feed conversion ratio of birds fed HSG were better (p<0.05) than those of subjects from HSF. Whether floury or granulated, HSB-diets have improved (p<0.05) these parameters compared to those of birds fed roasted and raw seed diets. The feed costs (per bird or kg carcass) obtained from HSC15, HST15, HSB15 were higher (p<0.05) than those of the HS0 unlike the gross margins realized. But, compared to HSC15 and HST15, these gross margins were higher (p<0.05) in HSB15 diets, with granulated in the lead. It was concluded that boiling rosella seeds, accompanied with pelletizing of diet containing them, significantly improved the growth performances and profit margin of broilers compared to roasted and raw rosella seeds diets.